Model to estimate lysine requirements of broilers - Siqueira, J. C. [UNESP]; Sakomura, N. K. [UNESP]; Gous, R. M.; Teixeira, I. A. M. A. [UNESP]; Fernandes, J. B. K. [UNESP]; Malheiros, E. B. [UNESP]; Sauvant, D.; VanMilgen, J.; Faverdin, P.; Friggens, N. (Wageningen Acad Publ, 2010)
The purpose of this study is to describe the development of a model to predict the digestible lysine requirements of broilers using the factorial approach, and to evaluate the model using as reference the model presented in Brazilian Tables for Poultry and Swine. The model partitions the requirement for maintenance and growth for feather-free body protein and feather protein, in which the inputs are body and feather protein weight and the daily rates of protein deposition in the feather-free body and feathers. The parameters that express the lysine requirement for maintenance were obtained in metabolism trials with roosters, and those for the efficiency of lysine utilization in experiments with broilers from 1 to 42 d. Based on these results the model proposed was: Lys (mg/d) = [(151xBP(m)(-0.27)xBP(t)) + (0.01xP(t)x18)] + [(75xBPD/0.77) + (18xFPD/0.77)], where Lys = digestible lysine requirement (mg/d), BPm=body protein weight at maturity (kg), BPt=body protein weight at time t (kg), FPt=feather protein weight at time t (kg), BPD=body protein deposition (g/d), FPD = feather protein deposition (g/d). The model yields sensible predictions of the digestible lysine requirements of broilers of different strains and ages growing at their potential, and suggests a lower lysine requirement after 27 d than does the Brazilian model. The proposed model is the first step in the development of a simulation model that predicts the food intake of a broiler and hence the dietary amino acid content that would optimise performance.
Keywords: amino acids; maintenance; modeling; performance; poultry